Orthodontic awareness amongst middle school teachers and parents of twin cities - Mansoor, Asma; Kasana, Mishaal Arshad; Nazir, Rozina; Siddiqui, Tania Arshad; Mansoor, Saad; Rahim, Shoaib (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the level of awareness towards orthodontic treatment among parents and teachers of middle school children. Method: The cross-sectional study was conducted from July 2021 to May 2022 in the middle schools of Rawalpindi and Islamabad, Pakistan, after approval from the ethics review committee of the Foundation University College of Dentistry and Hospital, Foundation University, Islamabad. Those included were middle school teachers and parents of students studying in middle schools. Data was collected using a validated questionnaire that had 6 demographic and 5 survey questions. The form was digitized for easy dissemination among parents. Data was analysed using SPSS 23. Results: Of the 240 subjects, 120(50%) each were parents and teachers. Overall, there were 165(68.75%) females and 75(31.25%) males. Level of education and professional exposure were not significantly different between teachers and parents (p>0.05). There was no difference in the level of education and professional work experience between the parents and teacher (p>0.05). Teachers showed a higher level of awareness than parents towards the role of orthodontist in tooth alignment (p=0.013), associated habits with malalignment of teeth (p=0.003), and that the most appropriate age for treatment was 10-15 years (p 0.001).Teachers were more likely of the opinion that facial disharmony is treatable than parents (odds ratio: 1.599, 95% confidence interval: 0.572-4.467). Conclusion: Teachers showed a higher level of awareness than parents regarding orthodontic treatment of children. Key Words: Awareness, Orthodontics, Middle school teachers, Parents, Attitude.